Pedagogical proposal "Emerging Community" to develop the scientific-technological competences of primary education students (SCIÉNDO INGENIUM, 2022)
The purpose of this research was to demonstrate that with the application of the “Emerging Community” pedagogical proposal, the scientific and technological competencies of primary-level students were significantly developed. The population consisted of 50 6th grade students from section “A” and “B”, selecting as a sample 25 students from group “A” because they were constituted groups. The applied design was pre-experimental. Three dimensions were measured as components of the scientific-technological competences, which are: planning, execution and presentation, for which a questionnaire was constructed and validated, which was applied as a pre-test and post-test. Descriptive and inferential statistics techniques, such as Student's t-test, were used for data processing. The conclusions indicate that the proposal significantly developed scientific and technological competences, in the planning dimension the students were located at the expected level in 40% (10) and 60% (15) superior achievement, in the execution dimension the 72% (18) in the expected level and 28% (7) in superior achievement and in the dimension of exposure in the expected level 84% (21) and in superior achievement 16% (4).
Keywords: Scientific skills; technological skills; emerging community; research capabilities; scientific attitude